2015
DOI: 10.3389/fncel.2015.00447
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 Regulates Hippocampal Plasticity Through Interaction with the Reelin Pathway, Glutamatergic Transmission and CREB Signaling

Abstract: Notch signaling plays a crucial role in adult brain function such as synaptic plasticity, memory and olfaction. Several reports suggest an involvement of this pathway in neurodegenerative dementia. Yet, to date, the mechanism underlying Notch activity in mature neurons remains unresolved. In this work, we investigate how Notch regulates synaptic potentiation and contributes to the establishment of memory in mice. We observe that Notch1 is a postsynaptic receptor with functional interactions with the Reelin rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 70 publications
2
69
0
Order By: Relevance
“…It was reported that Reelin has two major receptors: ApoER2 (apolipoprotein E receptor 2) and NMDAR (N-methyli-D aspartate receptor) to transfer signals. Notch1 could function as a postsynaptic receptor with functional interactions with these two receptors (41,42). Loss of Notch1 results in suppressing glutamatergic transmission and leads to decreased cAMP response element-binding signaling (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that Reelin has two major receptors: ApoER2 (apolipoprotein E receptor 2) and NMDAR (N-methyli-D aspartate receptor) to transfer signals. Notch1 could function as a postsynaptic receptor with functional interactions with these two receptors (41,42). Loss of Notch1 results in suppressing glutamatergic transmission and leads to decreased cAMP response element-binding signaling (42).…”
Section: Discussionmentioning
confidence: 99%
“…Notch1 could function as a postsynaptic receptor with functional interactions with these two receptors (41,42). Loss of Notch1 results in suppressing glutamatergic transmission and leads to decreased cAMP response element-binding signaling (42). Increased intracellular content of cAMP is closely related with the apoptosis of lymphocytes (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby RELN is crucial for synaptic plasticity and learning processes. Reelin-deficient mice show severe deficits in long-term potentiation and cognitive learning [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously shown that the loss of Notch1 from the CA1 subfield of the hippocampus of mice results in a significant impairment in LTP and LTD and a considerable deficit in hippocampus-dependent spatial memory. Furthermore, at a mechanistic level, we have shown that in the absence of Notch1, NMDA currents are significantly reduced and downstream activation of cAMP response element binding (CREB) protein is profoundly affected (Brai et al, 2015 ), likely accounting for the plasticity deficit. The Notch1-CREB axis has been prevously reported in fruit flies, where Notch1 protein has been shown to be essential for CREB hyperphosphorylation and its subsequent activation (Zhang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%